Value-based working capital management : determining liquid asset levels in entrepreneurial environments - Michalski, Grzegorz; SpringerLink (Online service). (New York : Palgrave Macmillan US, 2014)
Value-Based Working Capital Management analyzes the causes and effects of improper cash flow management between entrepreneurial organizations with varying levels of risk.
Keywords: Working capital; Cash management; Bookkeeping; Business enterprises -- Finance; Entrepreneurship; Investment banking; Securities; Risk management